Presentation and treatment of pediatric supracondylar fractures of the distal humerus at Prince Rashid ibn Al-Hasan Military hospital - Al-Qasaimeh, Motaz; Altaani, Ehab; Azzam, Ehab; Aldhoon, Mohammad; Alkarabsheh, Ahmad; Al-dweeri, Mohammad (International Journal of Research in Medical Sciences, 2023)
Background: A supracondylar humerus fracture (SCH) is one of the common fractures that are seen in the pediatric age group, with the most common age (5-7) years as described in the literature. Objectives was to study the presentation and treatment of SCH fractures in children at Prince Rashid bin Al Hassan Military Hospital, Jordanian Royal Medical Services. Methods: This study followed a retrospective design. Patients’ ages (1-14) years who attended the emergency department of Prince Rashid Hospital and were diagnosed with SCH were included in this study. All these patients’ data were statistically analyzed; descriptive analysis was performed for all variables. An association analysis used a chi-square test to find any association between the study variables and treatment modality variables. Results: The commonest age is 5 and 2 years; the male gender is more affected by the SCH fracture, and the left upper extremity is more affected by this fracture. The commonest direction of fracture displacement is posteromedial, with a percentage of 72.1%. Only 21.3% of SCH fractures required conservative treatment. The results showed an association between treatment modality and both directions of displacement and fracture type. Conclusions: A SCH fracture is one of the common fractures involving the pediatric age group that requires surgical intervention; 79.7% of cases require surgical intervention. Distal radius fracture is the most commonly associated injury with the SCH fracture. This study found an association between the treatment modality with both displacement direction and fracture type.